Meninos em risco na Amazónia: modelos de conduta desviante de jovens na gestão social - Chaves, J. F.; Reis, E.; Costa, J. (Sociologia: Tempo, indivíduo e sociedade, 2022)
The reality of the metropolitan area of Belém (RMB) in the state of Pará, located in the Amazon Region, is the object of study. The main objective of this thesis is to estimate the capacity of variables “leisure activities” (hedonist, instructive and playful), “family valuation” and “anomic feeling” to explain youth deviant behavior. In the method used was approached a structural equation modeling to estimate the models and their structures. This study points towards an innovative model of social management, in order to curb the deviant behavior of youth through social marketing strategies, consolidating a dedicated family structure, healthy leisure habits, motivational aspects an